Improved Outcome of Pythium Keratitis With a Combined Triple Drug Regimen of Linezolid and Azithromycin. Issue 7 (July 2021) - Sane, Sayali S.; Madduri, Bhagyasree; Mohan, Nitin; Mittal, Ruchi; Raghava, J. V.; Fernandes, Merle
Abstract : Purpose: To describe the clinical features, microbiological profile, and outcome of a series of cases of Pythium keratitis treated with topical and oral linezolid and topical azithromycin eye drops. Methods: This was a retrospective interventional case series of microbiologically and/or histopathologically proven cases of Pythium keratitis seen between October 2016 and December 2019. All patients received a combination of topical linezolid and/or azithromycin eye drops with oral linezolid. Analysis of demographic data, predisposing risk factors, microbiological results, treatment regimen, visual acuity, surgical intervention, and final outcome was performed. A subgroup analysis of cases >6 mm in size was performed. Success was defined as complete resolution on medical management. Failure was defined as worsening of infection necessitating therapeutic penetrating keratoplasty or evisceration. Results: Of 21 cases, 2 were lost to follow up, 1 was diagnosed on histopathology, and 1 received only topical linezolid. Characteristic microbiological features were noted on 10% potassium hydroxide calcofluor white wet mount in 20/21 (95.23%) and Gram stain in 18/21 (85.71%). On triple drug regimen, 14/17 cases (82.35%) resolved. Average time to resolution was 87.64 ± 44.44 days. More than 60% infiltrates (13/21) were large, and 66.66% infiltrates resolved in 109.3 ± 57.06 days. Of the 5 failures, 4 needed therapeutic keratoplasty and 1 needed evisceration. All grafts failed. Conclusions: The dual topical drug regimen with oral linezolid has good cure rates (over 80%) for Pythium keratitis over prolonged duration. It is recommended to persevere with medical therapy even in large infiltrates because more than two thirds resolved.